2019
DOI: 10.3126/jgmcn.v12i2.27172
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Contributing Factors of Low Back Pain among Nurses in Tertiary Level Hospital

Abstract: Background: Low back pain is one of the common musculoskeletal health problems that occur most commonly in nurses among all Health workers. Different researches showed that nurses are suffering from low back pain due to many factors. This research was conducted to find the prevalence and contributing factors of low back pain among nurses. Method: The descriptive cross-sectional study was done among 110 nurses by using stratified proportionate random sampling method. Semi structured self-administered ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Globally, low back pain is one of the common causes for the Disability Adjusted Life Years (DALYs) 8 and cause for frequent visits to hospital, as well as absence from work and activity. 9 In this study, the prevalence of LBP among commercial motorbike riders in last one year was 43.8%, the result was comparable with the study conducted in Nigeria among commercial motorcyclist that showed 41% experienced LBP. 5 In contrary to the current study findings, the LBP prevalence was higher among motorcyclist student in a university of Pakistan and police officer who rode motorcycle in Poland.…”
Section: Discussionsupporting
confidence: 82%
“…Globally, low back pain is one of the common causes for the Disability Adjusted Life Years (DALYs) 8 and cause for frequent visits to hospital, as well as absence from work and activity. 9 In this study, the prevalence of LBP among commercial motorbike riders in last one year was 43.8%, the result was comparable with the study conducted in Nigeria among commercial motorcyclist that showed 41% experienced LBP. 5 In contrary to the current study findings, the LBP prevalence was higher among motorcyclist student in a university of Pakistan and police officer who rode motorcycle in Poland.…”
Section: Discussionsupporting
confidence: 82%
“…The past studies from two of the major tertiary hospitals of Nepal; Sahid Gangalal National Heart Centre and Tribhuvan University Teaching Hospital revealed that 78% and 64.5% of the nurses experienced lower back pain. 24,25 Despite a higher prevalence of these disorders among the nurses which has affected their daily activities, only a few of them sought treatment. A similar observation was seen in the study from Bangladesh where out of all nurses who experienced lower back pain only 36.2% reported seeking medical care for their condition.…”
Section: Resultsmentioning
confidence: 99%
“…From these limited studies, the prevalence of lower back pain among nurses was observed to be around 60.0%-78.0%. [24][25][26] However, there is no evidence illustrating the overall rate of MSDs experienced by nurses in seven days and/or twelve months duration as well as its impact and determinants in these vulnerable populations. The occurrence of MSDs in the nursing population could impact the overall health system of the nation as nurses are one of the major health workforces.…”
Section: Introductionmentioning
confidence: 99%
“…Although the nursing profession is known to be a high risk for WMSDs, to the best of our knowledge, it is one of the least-studied occupations in Nepal (19). Determining the prevalence and factors associated with WMSDs among nurses as identified by problem analysis S1 Fig is important for hospital administrators, managers, healthcare workers, and health policymakers to reduce musculoskeletal discomfort among nurses and thereby achieve improved nursing performance.…”
Section: Introductionmentioning
confidence: 99%